Editorial - Mostert, Nicky (Journal of Health Informatics in Africa, 2024)
The Journal of Health Informatics in Africa is the official journal of the Pan African Health Informatics Association (HELINA) and publishes the proceedings of the HELINA conferences, as well as open-call issues. This issue is an open-call issue comprising of seven double blind peer reviewed papers submitted directly to the journal. Papers written in French are also published by the journal, and this issue includes one French paper. The year 2023 celebrates the 10th year since the first publication of a JHIA issue and as we celebrate this milestone we are continuously working on improving the quality of the journal. This issue includes the following papers: The paper by Osembe, Adebesin, and Smuts utilise thematic analysis to examine themes around the opportunities for digital innovation in healthcare. Author Nyarko recommends strategies to promote artificial intelligence adoption in healthcare decision-making among Ghanaian tertiary students. In the paper by Mohsam an analysis of nurses’ lived experience with digital health technologies in practice is shared. Key competencies for different levels of study and design considerations for a Health Informatics course are identified by authors Bhebe, De La Harpe, Kaura, and Kabaso. Author Awami evaluates users’ acceptance of a computer-based health information system at Benghazi diabetes centre. The paper by Abotsi, Agbemafleb, and Ayimeyc highlights positive outcomes and challenges associated with electronic health records systems at a Ghanaian hospital. The French paper by authors Randimbison, Rainibarijaona, Rajaonarison, and Rabenja highlights the impacts of a low-cost software for automated interpretation of fetal heart rate developed for the use in remote areas in low-income countries such as Madagascar. I would like to extend a very special thank you to the editorial team, authors, and peer-reviewers that made this issue possible. Nicky Mostert March 2024